PENINGKATAN PERILAKU HIDUP BERSIH DAN SEHAT DI SD NEGERI 31 JATI TANAH TINGGI KOTA PADANG - Masrizal Masrizal; Yudi Yudi; Mahesa Mahesa (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Clean and Healthy Living Behavior (PHBS) is motivated by the establishment of the Vision of Healthy Indonesia 2010 in the National Health System (SKN) as an integral part of the Long Term Development Plan for Health (RPJP-K) 2005-2025, through the Decree of the Minister of Health of the Republic of Indonesia. Number 131 / Menkes / SK / II / 2004. One of the PHBS arrangements is the arrangement of the school environment which is also in line with the world health promotion in educational institutions (health promoting school) launched by WHO. Based on observations, SD Negeri 31 Jati Tanah Tinggi is still not good enough in terms of clean and healthy living habits at school. There are still students who do not pay attention to their own health and the school environment. There are still those who throw garbage out of place, there are still students who don't wash their hands with soap before eating, and there are still many students who snack carelessly without paying attention to the hygiene of the food, and so on. With the formation and empowerment of the Healthy Schools Team, it is hoped that it can improve the behavior of clean and healthy living in schools. Not only that, through the formation and empowerment of the Healthy Schools Team, it is hoped that it can become a driving force in creating a clean and healthy school environment. The Healthy Schools team consists of students who meet the criteria and have been trained to participate in carrying out some of the efforts to maintain and improve the behavior of a clean and healthy life in the school environment. In general, the output target to be achieved in this service is to form and empower a Healthy Schools Team at SD Negeri 31 Jati Tanah Tinggi, Padang City, providing skills and knowledge about clean and healthy living habits from an early age. So that later this will become a pilot as a healthy school for other regions. This activity is in the form of socialization and counseling activities, the formation and empowerment of the "Healthy Schools" Team, the School PHBS Movement in the form of Evaluation and Sustainability of Program Implementation.